Spaces of Possibility In, Between, and Beyond Korea and Japan - Arai, Andrea 1956-; Sorensen, Clark W. 1948- (Seattle University of Washington Press, 2016)
"Arising from a 2012 conference, this volume engages with spaces in, between, and beyond the national borders of Japan and Korea--what Henri Lefebvre has called 'social spaces of possibility in which difference suddenly arises.' Some of these spaces involve the ambiguous longings and aesthetic refigurings of the past in the present, the new social possibilities that emerge out of the seemingly impossible new spaces of development, the opportunities of genre. Museums, colonial remains, new architectural spaces, graffiti, street theater, popular song, recent films, photographic topography, and translated literature all serve as keys for unlocking the ambiguous and contradictory--yet powerful--emotions of spaces, whether in Tokyo, Seoul, or New York. Rather than emphasizing individual countries, chapters focus on the relationship between Korea and Japan. This volume will appeal to readers interested in urban studies, Korean and Japanese studies, popular culture, anthropology, social history, and literature. Contributors are Janet Poole, Tom Looser, Chris Nelson, Robert Oppenheim, Heather Hindman, Kyoung-Lae Kang, John Whittier Treat, Franz Prichard, and Heekyoung Cho"--Provided by publisher.
Introduction: Movement, collaboration, spaces of difference / Andrea Gevurtz Arai and Clark W. Sorensen -- Part 1. Spaces of the colonial present -- The remains of colonial history / Janet Poole -- When is a prison like a folk art museum? : movement, affect, and the after-colonial in Seoul and Tokyo / Andrea Gevurtz Arai -- Part 2. Landscapes of the possible -- The global image : art, urbanism, and gathering politics in Korea, Japan, and the world / Tom Looser -- You were right about the stars : reading a history of war and occupation in the streets of Koza / Christopher T. Nelson -- Part 3. Restructuring place -- Mokp'o's tears : marginality and historical consciousness in contemporary South Korea / Clark W. Sorensen -- Economies of "soft power" : rereading waves from Nepal / Robert Oppenheim and Heather Hindman -- Embracing postcolonial potentiality : new faces of pro-Japanese collaborators in contemporary Korea / Kyoung-Lae Kang -- Part 4. Politics of the possible -- Chang Hyokchu and Japan's Koma Shrine : Koreans in Japan, past and present / John Whittier Treat -- Nakahira Takuma and the photographic topographies of possibility / Franz Prichard -- Translation and censorship : colonial writing and anti-imperial imagination of Asia in 1910s Korea / Heekyoung Cho.
Includes bibliographical references (pages 318-339) and index.
Donated by Korea Foundation
Keywords: Public spaces -- Japan -- Congresses; Public spaces -- Korea -- Congresses; Spatial behavior -- Japan -- Congresses; Spatial behavior -- Korea -- Congresses; Difference (Psychology) -- Social aspects -- Japan -- Congresses; Difference (Psychology) -- Social aspects -- Korea -- Congresses; Japan -- Relations -- Korea -- Congresses; Japan -- Social conditions -- Korea -- Congresses; Korea -- Relations -- Japan -- Congresses; Korea -- Social conditions -- Japan -- Congresses